Estudo do comportamento pós-crítico de paredes esbeltas de perfis metálicos - Sarmanho, Arlene Maria Cunha (1991)
The results from theorical-experimental studies of post-critical behaviour ofthin-walled cold-formed steel sections are presented. The experimental results are compared to theoretical predictions based on the effective width method and are used to assess several design prescriptions and past propositions. The experimental investigation incluedd tests of three specimens formed by lipped channel profiles under concentric loading. Based on the experimental measurements, a general formulation to describe the post-critical behaviour up to the failure was developed. The proposed formulation is compared to design codes prescriptions as well as some others approaches. The aplicability of the proposed formulation in numerical studies, with the help of a finite element code is analysed and compared to some other experimental results. Also the analysis and comparison with the experimental results are carried out to verify both the behaviour and the ultimate loads.